2008
DOI: 10.1016/j.bbrc.2007.12.104
|View full text |Cite
|
Sign up to set email alerts
|

The Ixodes scapularis salivary protein, salp15, prevents the association of HIV-1 gp120 and CD4

Abstract: Ixodes scapularis salivary protein, Salp15, inhibits CD4 + T cell activation by binding to the mostextracellular domains of the CD4 molecule, potentially overlapping with the gp120-binding region. We now show that Salp15 inhibits the interaction of gp120 and CD4. Furthermore, Salp15 prevents syncytia formation between HL2/3 (a stable HeLa cell line expressing the envelope protein) and CD4-expressing cells. Salp15 prevented gp120-CD4 interaction at least partially through its direct interaction with the envelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
(35 reference statements)
0
13
0
Order By: Relevance
“…For example, Salp15 facilitates transmission of the Lyme disease spirochete from the tick vector to the host [74]. However, it is unclear whether this is due to the binding of Salp15 to: (i) DC-SIGN on DCs, thus inhibiting the spirochete-induced production of pro-inflammatory cytokines by DCs and so modulating DC-induced T cell activation [27]; (ii) CD4, thereby inhibiting T cell activation [28], [75], [76]; and/or (iii) OspC, an outer surface protein on the spirochete, hence protecting the spirochete from antibody-mediated killing [77]. Likewise, Maxadilan promotes transmission of Leishmania parasites although the relative contribution of DC modulation to enhanced transmission is unresolved [78].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Salp15 facilitates transmission of the Lyme disease spirochete from the tick vector to the host [74]. However, it is unclear whether this is due to the binding of Salp15 to: (i) DC-SIGN on DCs, thus inhibiting the spirochete-induced production of pro-inflammatory cytokines by DCs and so modulating DC-induced T cell activation [27]; (ii) CD4, thereby inhibiting T cell activation [28], [75], [76]; and/or (iii) OspC, an outer surface protein on the spirochete, hence protecting the spirochete from antibody-mediated killing [77]. Likewise, Maxadilan promotes transmission of Leishmania parasites although the relative contribution of DC modulation to enhanced transmission is unresolved [78].…”
Section: Discussionmentioning
confidence: 99%
“…, 2006). In addition, because Salp15 binds to the most extracellular domains of the CD4 in a region that may overlap with the binding residues of the human immunodeficiency virus (HIV)‐1 envelope protein gp120, it is suggested that the domain may be bound with glycoprotein (Juncadella et al. , 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Because the regions of CD4 that interact with Salp15 and HIV-1 gp120 overlap, the question arises as to whether Salp15 could act as a competitive gp120 blocking agent. Another study (109) gave a positive answer to this hypothesis. In vitro microtiter and quantitative fusion assays showed that Salp15 blocks the interaction of gp120 and CD4 in a concentration-dependent manner, and the formation of syncytia by cells expressing gp120 and CD4 is significantly reduced in the presence of Salp15.…”
Section: Salp15 Blocks the Binding Of Hiv-1 Gp120 To Cd4mentioning
confidence: 95%
“…As mentioned above, the C-terminal portion (P11) of Salp15 is responsible for the binding of CD4. A previous study suggested that Salp15 competes with gp120 for an association with CD4, owing to spatial effects related to the interaction of the entire Salp15 protein with T cells, and not P11 (109). Nevertheless, P11 is able to bind to gp120, which is at least partly responsible for the competitive effect elicited by Salp15 (109).…”
Section: Salp15 Blocks the Binding Of Hiv-1 Gp120 To Cd4mentioning
confidence: 96%
See 1 more Smart Citation